ANALISIS KETIDAKAMANAN STREET FOOD DI SEPANJANG JALAN SILIWANGI - Hidayati, Lilik; Lina, Nur (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2017)
Street foods is one of common food for undergraduate students. There are many contaminat wich can contamined street foods, such as biological, phisical, and chemical contaminant. Many health problem can be caused by contaminated food. The purpose of this reseach is to indentify chemical contaminat in street foods that is sold in front of Siliwangi University, Siliwangi street. This research is  using survey method with 37 sample of street foods that are taken from 18  food?s seller. Chemical contaminant was indetify using food contaminat detection kit. Individual factor such as education, age, and income and also who is the producer of streets  were also measured in this study. Univariat analysis use the frequency distribution table, graph, and statistical calculation values. The result of this research are most of the responden?s education are yunior high school and senior high school. Average of respondens are 35 years old, and daily income are Rp 314.000,00. Most of the street foods is produced by the own seller. Chemical contaminat detection showed  borax and Rhodamin B aren?t detected. But formalin is found in two street foods. The recomendation are continue monitoring and ecducating food street?s seller abaout the impact of using chemical food additives.